Vehicular Traffic Air Pollution as Expressed by Leaves of Senna occidentalis (L.) Link from Three Busy Roads in Nigeria - Otoide, Jonathan Eromosele; Tedela, Patrick Olugbenga (Biological Sciences - PJSIR, 2017)
Matured leaves of Senna occidentalis (L.) were collected along the sides of busy roads of Oluku, Agbor and Sapele in Benin city, Nigeria where they were constantly exposed to air pollution from vehicular traffic (polluted populations). Others were collected from forest areas of Ebvomodu, Ebvoneka and Eyaen villages, each located within the distances of 50-60 km away from Benin city, where there was no source of vehicular air pollution(non-polluted populations). Peelings of the adaxial (upper) and the abaxial (lower) leaf epidermis were stained and microscopic examination and line drawings results showed that the leaves of the polluted populations suffered epidermal cell aberrations which ranged from plugged stomata, epidermal cell erosion and occasional leaf perforations caused by the corrosive activity of some of the pollutants as they undergo chemical reactions. These forms of damages were not observed in the non-polluted populations which were healthy with opened stomatal pores. At the upper (adaxial) epidermis, the mean lengths (µm) of stomatal pores of leaves of non-polluted populations of collections were 0.64 ± 0.41, 0.76 ± 0.84 and 0.74 ± 0.92, respectively and at the lower (abaxial) epidermis, the mean lengths were 0.61 ± 0.81, 1.40 ± 0.95 and 0.71 ± 0.81 from Ebvomodu, Ebvoneka and Eyaen, respectively. In the same vein, the mean width (µm) of pores of stomata of the non-polluted leaves collected from Ebvomodu, Ebvoneka and Eyaen were 1.14 ± 0.16, 0.32 ± 0.63 and 0.32 ± 0.11, respectively, at the upper (adaxial) epidermis. At the lower (abaxial) epidermis, the mean width (µm) of pores were 0.22 ± 0.25, 0.30 ± 0.51 and 0.39 ± 0.16 for collections from Ebvomodu, Ebvoneka and Eyaen, respectively. The stomatal pores of leaves of the polluted populations on the other hand were impossible to be measured because they were plugged by particulate air pollutants from the busy roads. It was opined that the leaves of the polluted populations would suffer eco-physiological stress by virtue of their plugged stomatal pores.